ANALISIS DAMPAK REVISI UANG KULIAH TUNGGAL (UKT) TERHADAP HASIL BELAJAR MAHASISWA PROGRAM STUDI PPKN UNIVERSITAS RIAU - Rovita, Lilis; Gimin, Gimin; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by: (1) there is always an increase in BKT every year; (2) the number of students who complained about the incompatibility of the UKT determination with the economic conditions of their families; (3) there is a change in the economic condition of the student's family, such as the presence of a family head who has died, who has been laid off, due to a decline or national economic problems, etc. which have resulted in a decrease in the economic capacity of students; and (4) the number of students who submitted a UKT revision was due to the inadequacy of the UKT previously set. This study aims to: (1) find out the learning outcomes of students of the Riau University PPKn Study Program before the revision of the Single Tuition Fee (UKT); (2) knowing the learning outcomes of the students of the Riau University PPKn Study Program after the revision of the Single Tuition Fee (UKT); and (3) determine the impact of the revised Single Tuition Fee (UKT) on student learning outcomes of the Riau University PPKn Study Program. This research is a quantitative survey method research, because this study aims to test the research hypothesis. This research was conducted on the campus of the University of Riau, where the population in this study were all PPKn students of 2016, 2017 and 2018 who were affected by the UKT revision, while the number of samples in this study was 30 people. Based on the research results, it is known that: (1) Student learning outcomes of the Riau University PPKn Study Program before the revision of the Single Tuition Fee (UKT) were achieved at an average value of 3.33 or with a quality value of